Chapter Hydrothermal Synthesis of Zinc Tin Oxide Nanostructures for Photocatalysis, Energy Harvesting and Electronics - Bento, Rovisco (InTechOpen, 2020)
The massification of Internet of Things (IoT) and Smart Surfaces has increased the demand for nanomaterials excelling at specific properties required for their target application, but also offering multifunctionality, conformal integration in multiple surfaces and sustainability, in line with the European Green Deal goals. Metal oxides have been key materials for this end, finding applications from flexible electronics to photocatalysis and energy harvesting, with multicomponent materials as zinc tin oxide (ZTO) emerging as some of the most promising possibilities. This chapter is dedicated to the hydrothermal synthesis of ZTO nanostructures, expanding the already wide potential of ZnO. A literature review on the latest progress on the synthesis of a multitude of ZTO nanostructures is provided (e.g., nanowires, nanoparticles, nanosheets), emphasizing the relevance of advanced nanoscale techniques for proper characterization of such materials. The multifunctionality of ZTO will also be covered, with special attention being given to their potential for photocatalysis, electronic devices and energy harvesters.